2017
DOI: 10.1002/ijc.30649
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cbl-dependent epidermal growth factor receptor degradation in Ling Zhi-8 suppressed lung cancer

Abstract: Activating mutation of epidermal growth factor receptor (EGFR) is correlated with malignant lung tumor. In our study, we demonstrated that recombinant LZ-8 (rLZ-8), a medicinal mushroom Ganoderma lucidum protein, induced cell cycle arrest and apoptosis by downregulating the expression of wild-type and mutated EGFR and inhibiting EGFR downstream effectors, AKT and ERK1/2 in lung cancer cells. We showed that rLZ-8 effectively inhibited lung cancer progression and suppressed EGFR expression of lung tumor lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…In our previous study, GMI inhibits EGF signaling pathway‐induced metastasis in lung cancer cells . LZ‐8, an immunomodulatory protein from Ganoderma lucidum, bound to EGFR to induce Cbl complexes‐mediated degradation of EGFR, resulting in the decrease of wild‐type and mutated EGFR expression in lung cancer cells . These publications prompt us to exam the inhibiting‐effect of GMI on β‐catenin in EGFR‐mutated lung cancer cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our previous study, GMI inhibits EGF signaling pathway‐induced metastasis in lung cancer cells . LZ‐8, an immunomodulatory protein from Ganoderma lucidum, bound to EGFR to induce Cbl complexes‐mediated degradation of EGFR, resulting in the decrease of wild‐type and mutated EGFR expression in lung cancer cells . These publications prompt us to exam the inhibiting‐effect of GMI on β‐catenin in EGFR‐mutated lung cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…LZ‐8, a fungal immunomodulatory protein from Ganoderma lucidium , suppresses EGFR‐mutant lung cancer cells via inhibiting the expression of EGFR . LZ‐8 reduces that metastasis of lung cancer through inhibiting FAK activity .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, rLz-8 might be a useful chemotherapeutic agent for the treatment of lung cancer because owing the key role of FAK targets in metastasis (Lin and Hsu, 2016 ). In addition, Lin et al reported a novel anticancer effect of rLz-8 through targeting EGFR mutation or overexpression and EGFR-dependent processes in lung cancer cells (Lin et al, 2017 ).…”
Section: Immunomodulatory Effects Of Ganoderma Andmentioning
confidence: 99%
“…It also served as a potential adjuvant for the development of DNA vaccines for human cancers owing to its stimulatory activity on dendritic cells ( Chu et al., 2011 ). Furthermore, the recombinant LZ-8 (rLZ-8) induced the degradation of epidermal growth factor receptor (EGFR) in a clathrin-mediated, endocytosis-dependent, and c-Cbl ubiquitination-dependent manner, which in turn, inhibited proliferation and promoted apoptosis of lung cancer cells ( Lin et al., 2017 ). Currently, the class of chemicals or proteins that exhibit the anti-cancer effects, as well as maintain the homeostasis of immune cells are not identified.…”
Section: Introductionmentioning
confidence: 99%